(untitled) (Global Journal of Human-Social Science, 2018)
The violence problem between 1940 and 1980 in Coast and Mountain Range, Michoacán, has been complex. The present paper argues that is easier to explain this kind of problem if we separate different waves and kinds of violence in this period: instrumental violence (agrarian violence, delinquency, drugs) and ritual violence (vendettas, pistolerismo). Every violence form has its own logic and temporality. But all of them are intertwined, sometimes with more intensity and other with less.